(untitled) (International Journal of Physiotherapy, 2015)
Background: Lateral Epicondylitis is the most common lesion of the elbow, affecting the tendinous origin of the wrist extensors. Although conservative treatment of this condition has been the subject of numerous studies, there is no agreement as to the most effective management strategy. Therefore, this study was designed to compare the efficacy of Cyriax physiotherapy Versus Eccentric Strengthening and Stretching exercises in reducing the pain and improving the grip strength and functional status of the affected extremity in chronic lateral epicondylitis. Method: An experimental study design, 60 subjects meeting the inclusion criteria were selected for the study and were randomly assigned into two groups: Group A (N=30) received Cyriax Physiotherapy and Group B(N=30) received Eccentric strengthening and static stretching of Extensor Carpi Radialis Brevis. Low Level Laser Therapy was a common treatment for both the groups. After 4 weeks of treatment, assessment was performed using Visual Analogue Scale (VAS), Hand Held Dynamometer (HHD) and Patient Rated Tennis Elbow Evaluation Questionnaire (PRTEE) at 0 week and at the end of 4 weeks. Results: Data analysis revealed that there is no statistically significant difference between the groups in VAS, HHD and PRTEE scores i.e. average improvement post treatment in both the groups are equal, but within group comparisons showed significant improvements in both the groups. Conclusion: The efficacy of Cyriax Physiotherapy is equal to Eccentric Strengthening and Stretching Exercises in chronic lateral epicondylitis.